Evaluating the Role of Family Learning Climate and Self-Related Skills as Determinants of Students’ Learning Resilience in the Digital Era - Nurhijriah; Fawzul Arifin; Alifah Muthmainna (Bulletin of Pedagogical Research, 2025)
The rapid development of digital technology has significantly transformed learning environments and created new challenges for students in maintaining academic resilience. Alongside increased access to information, students are also exposed to digital distractions, academic pressure, and reduced learning control, making learning resilience a critical competence in the digital era. Within this context, Family Learning Climate and Self-Related Skills, including self-regulation, self-efficacy, and emotional management, are assumed to play a central role in supporting students’ ability to adapt and persist in learning. This study aims to examine the influence of Family Learning Climate and Self-Related Skills on students’ learning resilience in a non-urban educational context in Indonesia. A quantitative research design was employed involving 160 students of SMA 1 Langgudu in the 2025/2026 academic year, selected from a population of 480 students using stratified random sampling. Data was collected through a five-point Likert-scale questionnaire and analyzed using descriptive statistics and multiple linear regression analysis. Instrument validity was ensured through expert judgment, and reliability testing produced Cronbach’s alpha values exceeding 0.80, indicating high internal consistency. The results indicate that the regression model is statistically significant (p < 0.001), confirming that Family Learning Climate and Self-Related Skills simultaneously influence learning resilience. Family Learning Climate contributes positively and significantly to learning resilience (β = 0.284, p = 0.001), while Self-Related Skills emerge as the stronger predictor (β = 0.316, p < 0.001). Furthermore, the model explains 19.2% of the variance in students’ learning resilience. These findings suggest that learning resilience is shaped by a synergy between family support as an external factor and intrapersonal capacity as an internal factor. The study highlights the need for educational policies and practices that strengthen parental involvement and intrapersonal skill development to foster resilient learners in the digital era.